Solid Lipid Nanoparticles (SLN): Formulation and Fabrication - Punu, Gabriella F.; Harahap, Yahdiana; Anjani, Qonita Kurnia; Hartrianti, Pietradewi; Donnelly, Ryan F.; Ramadon, Delly (Pharmaceutical Sciences and Research, 2023)
Solid lipid nanoparticles (SLN) have emerged as a novel drug delivery system and have been utilized for delivering various kinds of drugs since the 1990s. These particles may consist of multiple solid lipids, including glycerides, waxes, and fatty acids, and can be stabilized by a wide range of surfactants. SLN have garnered significant attention from researchers due to its innovative and versatile nature. Moreover, such delivery system has numerous advantages over traditional colloidal carriers, such as liposomes, polymeric nanoparticles, and emulsions. Several research groups have been developing SLN formulations and fabrication techniques based on their intended purpose, and this research number is still increasing globally. Given the vast potential for the development of SLN in the future, coupled with the wide variety of materials and techniques to be considered during the manufacturing process, this paper provides an extensive overview of the general introduction of SLN, their benefits and drawbacks, and the numerous excipients which can be associated with the SLN formulation. Various aspects related to the models of drug incorporation and fabrication methods are also systematically discussed in this review. In addition, an analysis of the factors that impact the stability of the SLN will also be documented to provide further insight for future advancements in SLN research.